Pengaruh Biofungisida terhadap Perakaran Stek Pucuk Jati di Persemaian UBH-KPWN Wonocatur, Bantul - , RITA WIDYA ASTUTI, Ir. Handojo Hadi Nurjanto, M.Agr.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The success of JUN (Jati Unggul Nusantara ) shoot cutting can be indicated by formation and growth of roots. Formation and growth of roots can be inhibited by the presence of root pathogens. In the JUN shoot cutting production, a biofungicide is used to prevent and control root pathogens. Biofungicide with different content of fungus, dosage, and carrier formulation can affect success of the JUN shoot cutting. Information about fungal content in the biofungicides and its dosage on rooting of shoot cutting are required. This research was conducted using RCBD (Randomized Completely Block Design). There were 9 treatments, namely: control (C), Biofungicide A 1 gram (A1D1), Biofungicide A 2 grams (A1D2), sterile Biofungicide A 1 gram (A0D1), sterile Biofungicide A 2 grams of (A0D2), Biofungicide B 1 gram (B1D1), Biofungicide B 2 grams (B1D2), sterile Biofungicide B 1 gram (B0D1), and sterile Biofungicide B 2 grams (B0D2). Each treatment was applied to 50 units shoot cuttings that were arranged in 2 blocks. The results showed that Biofungicide A contained 5.83x104 CFU/gram of fungi, consisted of 4 types of fungi namely Penicillium sp. (A), Trichoderma sp., Penicillium sp. (B), and Aspergillus sp. Biofungicide B contained 4.7 x104 CFU / gram of fungi, consists of 4 types of fungi namely Trichoderma sp. (A), Trichoderma sp. (B), Aspergillus sp., and yeast. Biofungicide A decreased survival percentage of shoot cutting and there was a tendency of causing reduction of rooting development. Application of Biofungicide B tended to increase shoot percentage and root development on both 1 gram and 2 grams of dosages. Whereas in the sterilized biofungicide (Tyndallisation method), thus containing killed fungus, tended to have better root development.